Failed Anti-Reflux Therapy Analysis of Causes and Principles of Treatment - Fisichella, P. Marco; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This multi-authored text provides information on the pathophysiology of Gastroesophageal Reflux Disease (GERD), appropriate medical management, and proper indications for and performance of surgical and endoscopic procedures. The Editors look at the current understanding of this disease, and present new information regarding tissue susceptibility, the role of bile and digestive enzymes, and cyclic changes in LES tone. Chapters are devoted to standard therapeutic options for GERD, including lifestyle changes, pharmacologic therapy, and surgery. In addition, newer endoscopic treatments including Stretta, Endocinch, injection of bulking agents, as well as others, are described. Failed Anti-Reflux Therapy: Analysis of Causes and Principles of Treatment is essential to any physician who manages patients with GERD, including internists, gastroenterologists, general surgeons, and thoracic surgeons.
History of medical and surgical antireflux therapy -- Establishing the diagnosis of GERD -- Medical management of gastroesophageal reflux disease: algorithms and outcomes -- Principles of successful surgical antireflux procedures -- Diagnosis and treatment of the extraesophageal manifestations of gastroesophageal reflux disease -- Acute complications of antireflux surgery -- Management of complications after paraesophageal hernia repair -- Persistent symptoms after antireflux surgery and their management -- Technical surgical failures: presentation, etiology, and evaluation -- Symptoms after antireflux surgery: everything is not always caused by surgery -- The medical and endoscopic management of failed surgical antireflux procedures -- Reoperation for failed antireflux surgery -- Management of the short esophagus -- Esophagectomy: indications, techniques, and outcomes. .
Keywords: Medicine; Gastroenterology; Surgery; Thoracic surgery; Medicine & Public Health; Gastroenterology; General Surgery; Thoracic surgery